2019
DOI: 10.14295/ras.v33i2.29252
|View full text |Cite
|
Sign up to set email alerts
|

Balanço hídrico em sistema hidrogeológico cárstico, região de Lagoa Santa, Minas Gerais

Abstract: A área estudada, APA Carste de Lagoa Santa e seus entornos, localiza-se a 35 km norte de Belo Horizonte abrange cerca de 505 km². A região tem sido alvo de vários empreendimentos que prever um aumento pela demanda de água, diante deste crescimento e da fragilidade do sistema carste é imprescindível o conhecimento do sistema hidrológico, tal como a compreensão balanço hídrico. Geologicamente, a região é representada por metacalcárias e metapelíticas neoproterozoicas do Grupo Bambuí, com rica densidade de feiçõe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The results obtained vary between 1.03 × 10 −4 and 2.81 × 10 −2 . It is observed that, in general, the data agree with what was found through pumping tests and have a median value of 3.29 × 10 −3 using De Paula and Velásquez (2019) rc values, and 3.96 × 10 −3 using 4 hydrological years, for all basins.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results obtained vary between 1.03 × 10 −4 and 2.81 × 10 −2 . It is observed that, in general, the data agree with what was found through pumping tests and have a median value of 3.29 × 10 −3 using De Paula and Velásquez (2019) rc values, and 3.96 × 10 −3 using 4 hydrological years, for all basins.…”
Section: Resultssupporting
confidence: 82%
“…In the study area, typical karst features are observed, associated with the carbonate rocks of the Sete Lagoas Formation. The occurrence of sinkholes, depressions, conduits, caves, poljes, and other morphological features reflects an evolved karst environment (De Paula & Velásquez, 2019). In addition, some of these features indicate the temporal evolution of the relief, with significant dissolution and subsidence, being important controllers of local hydrogeology, affecting recharge and subsurface flow (Pessoa, 2005).…”
Section: Geological and Hydrogeological Contextmentioning
confidence: 99%
“…The analyzed data correspond to the monitoring performed from October 2016 to September 2017, equivalent to a regional hydrological year at Lagoa Santa station, which has more than 50% of influence on the evaluated area (Paula and Velásquez 2019).…”
Section: Methodsmentioning
confidence: 98%
“…This potential is based on the degree of fracture, specific capacity measured in the region's tubular wells, and other parameters. Paula and Velásquez (2019) pointed out the importance of exposed and fractured carbonate massif zones with aquifer recharge, reaching average values for the area of 119 mm for the hydrological year 2016/2017. Ribeiro et al (2019) describe how the groundwater flow of the region is influenced by horizontal planes and eastward fractures.…”
Section: Physical Characteristics Of the Study Areamentioning
confidence: 99%
See 1 more Smart Citation